Unveiling ancient diversity of long-tailed wasps (Hymenoptera: Megalyridae): new taxa from Cretaceous Kachin and Taimyr ambers and their phylogenetic affinities - Brazidec, Manuel; Vilhelmsen, Lars; Boudinot, Brendon E.; Richter, Adrian; Hammel, Joerg U.; Perkovsky, Evgeny, E.; Fan, Yong; Wang, Zhen; Wu, Qiong; Wang, Bo; Perrichot, Vincent (Arthropod Systematics & Phylogeny, 2024)
International audience The Megalyridae are a small family of parasitoid wasps comprising eight extant genera (71 species) and six extinct genera (13 species). Here, we report eight new species from Late Cretaceous Kachin (Myanmar) and Taimyr (Russia) ambers; the family is recorded for the first time from the latter. dagger Cretolyra noijebumensis gen. et sp. nov., dagger Cretolyra shawi gen. et sp. nov., dagger Genkyhag innebula gen. et sp. nov., dagger Megacoxa chandrahrasa gen. et sp. nov., dagger Megacoxa janzeni gen. et sp. nov., and dagger Megacoxa synchrotron gen. et sp. nov., are described from late Albian - early Cenomanian Kachin amber; dagger Kamyristi exfrigore gen. et sp. nov. and dagger Kamyristi yantardakhensis gen. et sp. nov. from Taimyr amber (Baikura, late Albian - early Cenomanian Ognevka Formation and Yantardakh, Santonian Kheta Formation, respectively). Phylogenetic analyses of the family are presented and the classification of the Megalyridae is revised accordingly. A new tribe, dagger Megalavini trib. nov., is erected to accommodate dagger Cretolyra gen. nov., dagger Genkyhag gen. nov., dagger Megacoxa gen. nov. together with dagger Megalava Perrichot, 2009; dagger Megalavini trib. nov. is characterized by the vein M fully pigmented and veins Rs+M and M+Cu aligned, the crenulate mesometapectal sulcus, and the pronotal spiracle not posteriorly surrounded by cuticle. This spiracular condition was previously only observed in dagger Megazar Perrichot, 2009, thus the subfamily dagger Megazarinae Perrichot, 2009 stat. nov. is proposed for the clade (dagger Megalavini + dagger Megazar), as sister to the remaining Megalyridae. The latter is defined as the Megalyrinae, with dagger Kamyristi gen. nov. being retrieved as sister to all other genera except Rigel Shaw, 1987 under parsimony analyses. To align phylogeny with classification, three new tribes are erected (dagger Kamyristini trib. nov., dagger Megallicini trib. nov., and dagger Valaaini trib. nov.) and the dagger Cretodinapsini is ...